2017
DOI: 10.1371/journal.pone.0178370
|View full text |Cite
|
Sign up to set email alerts
|

Functional interaction between co-expressed MAGE-A proteins

Abstract: MAGE-A (Melanoma Antigen Genes-A) are tumor-associated proteins with expression in a broad spectrum of human tumors and normal germ cells. MAGE-A gene expression and function are being increasingly investigated to better understand the mechanisms by which MAGE proteins collaborate in tumorigenesis and whether their detection could be useful for disease prognosis purposes. Alterations in epigenetic mechanisms involved in MAGE gene silencing cause their frequent co-expression in tumor cells. Here, we have analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…This assertion is sustained by the fact that the MAGE family (melanoma antigen genes-A) are expressed both in melanoma and in prostate cancer. In 2017, it was demonstrated that MAGE-A proteins can potentiate specific oncogenic processes being involved in several unrelated cancers due to the complex MAGE gene network [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…This assertion is sustained by the fact that the MAGE family (melanoma antigen genes-A) are expressed both in melanoma and in prostate cancer. In 2017, it was demonstrated that MAGE-A proteins can potentiate specific oncogenic processes being involved in several unrelated cancers due to the complex MAGE gene network [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, suppressing MAGEA12 expression decreased the migratory and invasive capacities of both cell lines, notwithstanding the differences between the lines in terms of migration and invasion (Figure 4b,c). In addition, we showed that MAGEA12 silencing reduced breast cancer aggressiveness by using a 3D culture system that can identify aggressive characteristics based on a cell shape classification [32][33][34]. Thus, siRNA-mediated MAGEA12 knockdown not only dramatically reduced the expression of MAGEA12, but it also changed the morphology of the cell clusters from their usual aggressive grape-like phenotype to the less aggressive rounded/mass cluster phenotype (Figure 4d).…”
Section: Effect Of Magea12 Silencing and Overexpression On Breast Cancer Cell Aggressivenessmentioning
confidence: 87%
“…This may reflect their close location on the X chromosome [29,30]. In particular, MAGEA3 and MAGEA6 expression are highly correlated in colon and lung cancer [31], as is MAGEA6 and MAGEA11 expression in prostate cancer [32]. However, it is not clear whether, and which, MAGE-A members are simultaneously expressed in breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, co-expression of structurally similar MAGE proteins can regulate a large number of oncogenic functions. Nevertheless, functional interaction of two MAGE proteins to perform a single oncogenic function has also been reported ( 43 ). Furthermore, both MAGEH1 and Necdin have been shown to interact with p75 neurotrophin receptors, a class of receptors that regulate cell growth and neuronal survival ( 44 ).…”
Section: Discussionmentioning
confidence: 99%